Enhancing School Quality in Vietnam through Participative and Collaborative Learning - Parandekar, Suhas D. (World Bank, Washington, DC, 2017)
The Vietnam Escuela Nueva (VNEN) program incorporates and integrates several innovative and globally recognized practices including: (a) Participative and collaborative learning; (b) Self-paced learning guides; (c) Student government; (d) Formative assessment; (e) Application or real-life oriented learning, with community integration; and (f) Teacher professional networks. The combination of these elements is intended to spur a transformative and powerful learning experience that produces the kinds of new skills and competencies expected of children in the 21st century. This report presents the findings and conclusions of an Impact Evaluation (IE) study of the VNEN program. The study compares the experience of students and school communities from VNEN schools with the experience from a randomly selected comparators group of traditional schools. The cohort comparison of children from third grade to fifth grade shows that the VNEN program positively impacted both non-cognitive and cognitive skills of the students.